Mild and Efficient Reduction of Organic Carbonyl Compounds to their Corresponding Alcohols with Zn(BH4)2 Under Protic Condition - Setamdideh, Davood; Khezri, Behrooz; Rahmatollahzadeh, Mehdi; Ali Poramjad, Avat (Asian Journal of Chemistry, 2012)
Zn(BH4)2 (1-2 mmol) in wet THF or CH3CN reduces varieties of organic carbonyl compounds such as aldehydes, ketones, acyloins, a-diketones and a, b-unsaturated carbonyl compounds to their corresponding alcohols. Reduction reactions were carried out in wet THF at room temperature in high to excellent yields of products. The chemoselective reduction of aldehydes over ketones was accomplished successfully. In addition, regioselectivity and exclusive 1,2- reduction of conjugated carbonyl compounds to their corresponding allylic alcohols in high to excellent yields was accomplished successfully with this reducing system.